A Tourism Development Strategic Model for Optimizing Village Fund Allocation in Baguk Island, Pulau Banyak, Aceh Singkil - Syukri; Haerul Warisin; Muhammad Gusti; R. Dewi Setiani; Mawar; Azhari Aziz Samudra (International Journal of Educational Research Excellence, 2026)
This study aims to develop a strategic model for tourism development through optimizing village fund utilization in Pulau Bagukk, Pulau Banyak Subdistrict, Aceh Singkil Regency, with a focus on financial management perspectives. Despite having significant marine tourism potential, the development of tourism in this area remains suboptimal due to structural and managerial constraints, including limited human resource capacity, weak institutional frameworks, and ineffective allocation of village funds. This research employs a mixed-methods approach, combining qualitative and quantitative data to explore the existing conditions and formulate a comprehensive strategy. Data were collected through in-depth interviews, observations, documentation, and questionnaires. The analytical framework integrates key international theories, including Community-Based Tourism as proposed by Peter E. Murphy, Sustainable Tourism framework by United Nations World Tourism Organization, and Collaborative Governance model developed by Chris Ansell and Alison Gash. Additionally, this study incorporates public financial management principles such as efficiency, effectiveness, and value for money. The findings reveal that village fund utilization is predominantly focused on physical infrastructure, with limited investment in human capital, digital promotion, and institutional strengthening. This condition results in suboptimal economic outcomes and limited community empowerment. Furthermore, the lack of integrated governance and sustainability practices hinders the long-term development of tourism. The study proposes an integrative strategic model that combines Community-Based Tourism, Sustainable Tourism, and Collaborative Governance, supported by optimized village fund allocation as a financial instrument. This model emphasizes capacity building, digital transformation, tourism product development, and institutional strengthening. The novelty of this research lies in integrating tourism development theories with public financial management, positioning village funds as a catalyst for sustainable and inclusive local economic transformation. The findings contribute both theoretically and practically by providing a comprehensive framework for village-based tourism development in coastal and island regions